Hubungan Paparan Timbal dengan Kejadian Gangguan Fungsi Hati Pada Pekerja Pengecoran Logam di CV. Sinar Baja Cemerlang Desa Bakalan, Ceper Kabupaten Klaten - Minarti, Fitra Ayu; Setiani, Onny; Joko, Tri (Jurnal Kesehatan Lingkungan Indonesia, 2015)
Background : Lead ( Pb ) is a toxic material which can accumulate in the human body and can be detrimental to health and cause damage to various organs including the liver. Results of a preliminary study in CV. Sinar Baja Cemerlang obtained Pb in the worker's blood showed that exceeds the threshold value determined by the CDC.Methode : Cross-sectional study was conducted on 33 subjects research at CV . Sinar Baja Cemerlang Bakalan Village, Ceper, District Klaten. In this research, working time, length of work every day and Pb levels in the blood as independent variables and parameters of liver function (SGOT, SGPT and Gamma GT) as the dependent variable. Data were collected through observation, interviews, and laboratory examinations. Analysis was done using univariate and bivariate analysis.Result : Univariate analysis results obtained an average blood levels of Pb in 24.39 µg/dL and 84.8 % of respondents experienced an incident impaired liver function. Spearman test results showed significant association between working time with the level of ALT (p = 0.005) and Gamma-GT (p = 0.017), whereas the other variables did not show any significant associations. Conclution : There is no significant association between type of work, working time, length of work every day and Pb levels in the blood with incidence of liver disfunction in metal foundry workers in CV. Sinar Baja Cemerlang Bakalan Village, Ceper, District Klaten. Keywords : Lead exposure, Liver Disfunction